ANALISIS DETERMINAN PROFITABILITAS PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Cindy Restadila (2020)
This study aims to the effect of capital adequacy, credit risk and liquidity on the profitability of banks listed on the Indonesia Stock Exchange in the period 2015-2019.. The data used are secondary data in the form of annual financial statements. Data collection was taken using documentation techniques sourced from bank publication reports. The samples used in this study were 41 samples taken using saturated sampling techniques. This study uses panel data regression analysis. The results showed that the capital adequacy measured by the Capital Adequacy Ratio (CAR) had a negative effect on profitability (ROA). Credit risk as measured by Non-Performing Loans (NPL) has a negative effect on profitability (ROA). Liquidity as measured by Loan to Deposit Ratio (LDR) has no effect on profitability (ROA).